CORPORATE SOCIAL RESPONSIBILITY: MALAYSIAN CORPORATE LEADERS’ UNDERSTANDING - Eric Balan; Mohammad Saeed (Universitas Gunadarma, 2021)
Corporate Social Responsibility commonly known as CSR has been defined by many world organizations and at present its definition has been practiced and adopted by corporations based on individual’s belief and understanding. Every corporation has its own definition of CSR and what is deemed CSR has always been philanthropy, cause-related marketing, green, community outreach or piecemeal solution. This paper will examine the understanding of CSR between the current and future corporate leaders and to analyze the challenges of its applications and implications in Malaysia. Through interviews and surveys, we analyze how CSR is perceived and how the dynamics are influenced by the interest of a corporation itself. In this paper we hope to highlight that the future of CSR is in the hands of the younger generation as they take on the role of corporate leaders. The corporate leaders of today’s economy will have a distinctive role in accompanying the younger generation into the arena of CSR to establish a foundation for the future of CSR in Malaysia that will take shape as a culture and identity. In conclusion, based on the Malaysian understanding of CSR, the authors suggest CSR approaches that will respond to the needs of communities in emerging economies.